2016
DOI: 10.5604/17331331.1215612
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizobial Bacteria Nodulating Astragalus corrugatus and Hippocrepis areolata in Tunisian Arid Soils

Abstract: A b s t r a c tFifty seven bacterial isolates from root nodules of two spontaneous legumes (Astragalus corrugatus and Hippocrepis areolata) growing in the arid areas of Tunisia were characterized by phenotypic features, 16S rDNA PCR-RFLP and 16S rRNA gene sequencing. Phenotypically, our results indicate that A. corrugatus and H. areolata isolates showed heterogenic responses to the different phenotypic features. All isolates were acid producers, fast growers and all of them used different compounds as sole car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(78 reference statements)
0
11
1
Order By: Relevance
“…Concerning Rhizobium, our isolates were closely related to R. sullae, which was known to nodulate Hedysarum coronarium L. [40], and to R. pakistanense, recovered from groundnut nodules in Pakistan [41]. Ensifer strains were related to E. meliloti, a common microsymbiont of most wild legumes in Tunisian arid soils [39,42,43]. Isolates belonging to Phyllobacterium have been previously described to nodulate wild legumes in Tunisia [7,38,43].…”
Section: Rhizobia Isolated From C Villosa Nodules In Tunisian Arid Smentioning
confidence: 65%
“…Concerning Rhizobium, our isolates were closely related to R. sullae, which was known to nodulate Hedysarum coronarium L. [40], and to R. pakistanense, recovered from groundnut nodules in Pakistan [41]. Ensifer strains were related to E. meliloti, a common microsymbiont of most wild legumes in Tunisian arid soils [39,42,43]. Isolates belonging to Phyllobacterium have been previously described to nodulate wild legumes in Tunisia [7,38,43].…”
Section: Rhizobia Isolated From C Villosa Nodules In Tunisian Arid Smentioning
confidence: 65%
“…A polyphasic approach analysis indicated that bacterial strains isolated from the pasture legume Biserrula pelecinus growing in Morocco belong to the genus Mesorhizobium. At Tunisia, Mahdhi et al [47] showed that five strains isolated from Astragalus corrugatus were phylogenetically related to M. temperatum and to Mesorhizobium sp. From the tribe Galegeae (subtribe Coluteinae), Ourarhi et al [48] reported that Colutea arborescens is nodulated by diverse rhizobia in Eastern Morocco, among them, the genus Mesorhizobium.…”
Section: The Genus Mesorhizobium (Phyllobactericeae)mentioning
confidence: 99%
“…E. meliloti and E. numidicus strains were isolated from the Genisteae tribe such as Argyrolobium uniflorum, Retama raetam, and Genista saharae [56][57][58]69]. For Galegae tribe, Mahdhi et al [47] reported that rhizobial symbionts of Astragalus corrugatus are closely related to E. meliloti under Tunisian soils. From the Hedysareae tribe, Mahdhi et al [35] reported that strains isolated from Hedysarum spinosissimum root nodules are closely related to E. meliloti in the infra-arid zone of Tunisia.…”
Section: The Genus Ensifer (Sinorhizobium) (Rhizobiaceae)mentioning
confidence: 99%
See 2 more Smart Citations